Exposure to a SARS-CoV-2 infection at work: development of an international job exposure matrix (COVID-19-JEM) - Oude Hengel, Karen M; Burdorf, Alex; Pronk, Anjoeka; Schlünssen, Vivi; Stokholm, Zara A; Kolstad, Henrik A; van Veldhoven, Karin; Basinas, Ioannis; van Tongeren, Martie; Peters, Susan (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVE ': 'This study aimed to construct a job exposure matrix (JEM) for risk of becoming infected with the SARS-CoV-2 virus in an occupational setting. ' ' METHODS ': 'Experts in occupational epidemiology from three European countries (Denmark, The Netherlands and the United Kingdom) defined the relevant exposure and workplace characteristics with regard to possible exposure to the SARS-CoV-2 virus. In an iterative process, experts rated the different dimensions of the COVID-19-JEM for each job title within the International Standard Classification of Occupations system 2008 (ISCO-08). Agreement scores, weighted kappas, and variances were estimated. ' ' RESULTS ': 'The COVID-19-JEM contains four determinants of transmission risk [number of people, nature of contacts, contaminated workspaces and location (indoors or outdoors)], two mitigation measures (social distancing and face covering), and two factors for precarious work (income insecurity and proportion of migrants). Agreement scores ranged from 0.27 [95% confidence interval (CI) 0.25–0.29] for ‘migrants’ to 0.76 (95% CI 0.74–0.78) for ‘nature of contacts’. Weighted kappas indicated moderate-to-good agreement for all dimensions [ranging from 0.60 (95% CI 0.60–0.60) for ‘face covering’ to 0.80 (95% CI 0.80–0.80) for ‘contaminated workspaces’], except for ‘migrants’ (0.14 (95% CI -0.07–0.36). As country differences remained after several consensus exercises, the COVID-19-JEM also has a country-axis. ' ' CONCLUSIONS ': 'The COVID-19-JEM assesses the risk at population level using eight dimensions related to SARS-COV-2 infections at work and will improve our ability to investigate work-related risk factors in epidemiological studies. The dimensions of the COVID-19-JEM could also be valuable for other future communicable diseases in the workplace.
Keywords: COVID-19; COVID-19-JEM; infection at work; JEM; job exposure matrix; mitigation factor; precarious work; SARS-Cov-2; transmission risk; variance